Islamic home financing instruments in Malaysia: the emerging issue of financial (Un)affordability - Md Zabri, Mohd Zaidi; Haron, Razali (2018)
This study compares and contrasts Islamic home financing instruments such as bay bithaman ajil and musharakah mutanaqisah (MM) by Islamic commercial banks, government-owned home financing institution and financial cooperative. Mathematical simulations were carried out in examining the purchase- and repayment-affordability of Islamic home financing instruments by the above-mentioned providers. We have shown that Islamic home financing instruments by Islamic commercial banks are an unaffordable option for most Malaysians, even vis-à-vis the conventional home loan. Although government-owned home financing institution provides the cheapest option for homeowners, it is, however, restricted to civil servants. MM by the financial cooperative, on the other hand, is a workable, more financially affordable option to potential homeowners. The reason for this is that, unlike Islamic commercial banks, MM uses rental rates as a benchmarking tool which is more flexible as well as more responsive to its member-customers’ specificities of localities and types of homes. As a result, it may reduce the cost of home acquisition (purchase-affordability) and the amount of monthly instalments (repayment-affordability) by homeowners in Malaysia.